Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10067-006-0304-4
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of hypermobility and its relationship with clinical findings of fibromyalgia patients

Abstract: The etiology and pathogenic mechanisms of fibromyalgia (FM) are unknown. A number of studies have suggested that there was a link between hypermobility and FM. In this study, we aimed to expose the frequency of hypermobility in FM patients and its relation with clinical findings. For this reason, 236 women (118 FM women as study group and 118 healthy women as control group) were enrolled in the study. Joint hypermobility was evaluated in the participants by using Beighton scoring system. The rate of joint hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 15 publications
1
49
2
3
Order By: Relevance
“…Most of the women in the sample were classified within the population average, independent of FMS, a result that disagrees with evidence indicating that FMS is associated with joint hypermobility [24][25][26] . As described when presenting the protocol, in the Flexitest, each assessed movement is scored from 0 (lowest range of motion) to 4 (largest range of motion).…”
Section: Discussioncontrasting
confidence: 82%
“…Most of the women in the sample were classified within the population average, independent of FMS, a result that disagrees with evidence indicating that FMS is associated with joint hypermobility [24][25][26] . As described when presenting the protocol, in the Flexitest, each assessed movement is scored from 0 (lowest range of motion) to 4 (largest range of motion).…”
Section: Discussioncontrasting
confidence: 82%
“…[8] The coexistence of HMS and FMS has been shown in previous studies in which it was suggested that hypermobility may play a prominent role in the pathogenesis of pain in women with FMS. [9][10][11][12] It has also been reported that FMS is associated with balance problems and increased fall frequency. [13] To the best of our knowledge, at the present time no published reports have specifically reported the relationship between hypermobility and balance in patients with FMS.…”
Section: Discussionmentioning
confidence: 99%
“…[13,24,25] In addition, a strong association exists between FMS and hypermobility. [9][10][11][12] Hypermobility syndrome is a systemic disorder which affects virtually all joints, and the lack of proprioception is a wellknown feature. [6,7] Impaired joint proprioception can lead to poor postural control and balance in patients with HMS, as has been previously demonstrated by the research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bridges et al [24] found joint hypermobility in 15% of adult patients referred to a rheumatologist. Moreover, Ofluoğlu et al [25] and Şendur et al [26] found a BJHS rate of 64.2% and 46.6% respectively in women with fibromyalgia, and Nijs et al [27] reported a GJH rate of 20.6% in 68 cases with chronic fatigue syndrome and a rate of 4.3% in the healthy control group. Furthermore, Aktaş et al [28] demonstrated that BJHS is a predisposing factor for carpal tunnel syndrome, and Bird et al [29] found that there was an increased risk of OA due to joint overloading associated with an abnormal increase in joint ROM and decreased proprioception in cases with BJHS.…”
Section: Discussionmentioning
confidence: 98%